2022
DOI: 10.1017/s0272263122000377
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study into learners’ productive collocation knowledge in L2 German and factors affecting the learning

Abstract: This longitudinal study explored the roles of item- and learner-related variables in L2 learners’ development of productive collocation knowledge (L1 = Dutch; L2 = German; NLearners= 50). Learners’ form recall knowledge of 35 target collocations was measured three times over a 3-year period. The item-related variables investigated were L1-L2 congruency, corpus frequency, association strength, and imageability. We also explored the learner-related variables L2 prior productive vocabulary knowledge and L2 immers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…L2 learners tend to rely on using literal translation equivalents, which often results in unnatural and even odd collocations. Congruency, defined as "the presence or absence of a literal L1 translation equivalent" (Peters, 2016, p. 114) has indeed proved to be an influencing factor when it comes to the acquisition, processing or use of collocations (Boone et al, 2023;Ding & Reynolds, 2019;Vu & Peters, 2022;Wolter & Gyllstad, 2013). A further factor is the lack of exposure to the target language (Durrant & Schmitt, 2010), and it has been demonstrated that numerous encounters are needed before a collocation is learned (Vilkaitė, 2017).…”
Section: Collocations In L2 Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…L2 learners tend to rely on using literal translation equivalents, which often results in unnatural and even odd collocations. Congruency, defined as "the presence or absence of a literal L1 translation equivalent" (Peters, 2016, p. 114) has indeed proved to be an influencing factor when it comes to the acquisition, processing or use of collocations (Boone et al, 2023;Ding & Reynolds, 2019;Vu & Peters, 2022;Wolter & Gyllstad, 2013). A further factor is the lack of exposure to the target language (Durrant & Schmitt, 2010), and it has been demonstrated that numerous encounters are needed before a collocation is learned (Vilkaitė, 2017).…”
Section: Collocations In L2 Learningmentioning
confidence: 99%
“…A further factor is the lack of exposure to the target language (Durrant & Schmitt, 2010), and it has been demonstrated that numerous encounters are needed before a collocation is learned (Vilkaitė, 2017). Some learners, however, seem to deal with these difficulties better than others, since large individual variation in collocation knowledge has been observed (Boone et al, 2023;González Fernández & Schmitt, 2015;Li & Schmitt, 2010). This variation might partially be the result of individual differences that are assumed to influence L2 learning at various levels (Dörnyei, 2005).…”
Section: Collocations In L2 Learningmentioning
confidence: 99%
See 3 more Smart Citations